Buddhist Contribution to Healthy Living - Karunasagara, D.K.M.K. (University of Sri Jayewardenepura, Nugegoda., 2015)
The Buddhist statement “ārogyāparamālābhā” means a healthy life is the best gain, and there are a number of facts which provide evidence to prove it. According to the article 25 of the United Nations Universal Declaration of Human Rights 1948, everyone has the right to a standard of living adequate for the health and well-being of himself and of his family. In this paper, I wish to discuss the Buddhist contribution to healthy living in three main areas such as 1) Physical health protection, 2) Mental health protection and 3) Natural resources as voluntary protectors of humans. Physical health protection is fulfilled with the combination of self-clean, essential nourishment method, pure water supplement to the body and self-protection from social diseases such as sexual diseases and other infectious diseases. The Buddhist approach provides an avenue to reduce physical problems. 1. Increasing morality, importance of counselling and providing the knowledge of gender equality increase mental health protection. Buddhist suttas also point out the importance of the development of inner peace. 2. Buddhism has a close relationship with the environment. Human existence depends on the way we use natural resources. 3. Ensuring environmental sustainability according to Buddhism provides friendliness for mankind. To conclude, global responsiveness to develop the health level of the Third World countries has become a special requirement of the current world. Buddhism which has more than 2,500 years of proud history still contributes to the development of a better human existence in a modern technical world.
Keywords: Morality; Counselling; Gender equality; Environmental sustainability; Buddhism